无需命令即可将文档更改为斜体

无需命令即可将文档更改为斜体

我正在写一篇数学论文,在写了一些例子之后,我用来描述某些现象的纯文本变成了斜体。如何让文档使用默认字体书写?在此处输入图片描述

您可以看到斜体字从 0.1.2 预备阶段开始。以下是该论文的代码

\documentclass[]{book}

%These tell TeX which packages to use.
\usepackage{array,epsfig}
\usepackage{amsmath}
\usepackage{amsfonts}
\usepackage{amssymb}
\usepackage{amsxtra}
\usepackage{amsthm}
\usepackage{mathrsfs}
\usepackage{color}

%Here I define some theorem styles and shortcut commands for symbols I use often
\theoremstyle{definition}
\newtheorem{defn}{Definition}
\newtheorem{thm}{Theorem}
\newtheorem{cor}{Corollary}
\newtheorem*{rmk}{Remark}
\newtheorem{lem}{Lemma}
\newtheorem*{joke}{Joke}
\newtheorem{ex}{Example}
\newtheorem*{soln}{Solution}
\newtheorem{prop}{Proposition}

\newcommand{\lra}{\longrightarrow}
\newcommand{\ra}{\rightarrow}
\newcommand{\surj}{\twoheadrightarrow}
\newcommand{\graph}{\mathrm{graph}}
\newcommand{\bb}[1]{\mathbb{#1}}
\newcommand{\Z}{\bb{Z}}
\newcommand{\Q}{\bb{Q}}
\newcommand{\R}{\bb{R}}
\newcommand{\C}{\bb{C}}
\newcommand{\N}{\bb{N}}
\newcommand{\M}{\mathbf{M}}
\newcommand{\m}{\mathbf{m}}
\newcommand{\MM}{\mathscr{M}}
\newcommand{\HH}{\mathscr{H}}
\newcommand{\Om}{\Omega}
\newcommand{\Ho}{\in\HH(\Om)}
\newcommand{\bd}{\partial}
\newcommand{\del}{\partial}
\newcommand{\bardel}{\overline\partial}
\newcommand{\textdf}[1]{\textbf{\textsf{#1}}\index{#1}}
\newcommand{\img}{\mathrm{img}}
\newcommand{\ip}[2]{\left\langle{#1},{#2}\right\rangle}
\newcommand{\inter}[1]{\mathrm{int}{#1}}
\newcommand{\exter}[1]{\mathrm{ext}{#1}}
\newcommand{\cl}[1]{\mathrm{cl}{#1}}
\newcommand{\ds}{\displaystyle}
\newcommand{\vol}{\mathrm{vol}}
\newcommand{\cnt}{\mathrm{ct}}
\newcommand{\osc}{\mathrm{osc}}
\newcommand{\LL}{\mathbf{L}}
\newcommand{\UU}{\mathbf{U}}
\newcommand{\support}{\mathrm{support}}
\newcommand{\AND}{\;\wedge\;}
\newcommand{\OR}{\;\vee\;}
\newcommand{\Oset}{\varnothing}
\newcommand{\st}{\ni}
\newcommand{\wh}{\widehat}

%Pagination stuff.
\setlength{\topmargin}{-.3 in}
\setlength{\oddsidemargin}{0in}
\setlength{\evensidemargin}{0in}
\setlength{\textheight}{9.in}
\setlength{\textwidth}{6.5in}
\pagestyle{empty}

\begin{document}

\begin{center}
{\Large Hypergeometric Bernoulli Numbers via Umbral Calculus}\\
\textbf{Christopher Ernst}\\ %You should put your name here
Begun: 5-5-2017 %You should write the date here.
\end{center}

\vspace{0.2 cm}

\section{Introduction}

\subsection{Preliminaries - Action of a Formal Power Series on Polynomials}

Let $f(t)=\sum_{j=0}^\infty{a_j\frac{t^j}{j!}}\in \mathcal{F}$ be a formal power series where $a_j\in \mathbb{F}$ where $char(\mathbb{F})=0$ and let $p(x)=\sum_{k=0}^n{c_kx^k}\in P$, the algebra of polynomials of a single variable over $\mathbb{C}$.  We know then that $P^*$ is the vector space of all linear functionals on $P$.  The notation 

$$ \langle L \mid p(x) \rangle $$

is used to denote the action of a linear functional $L$ on a polynomial $p(x)$.  As $P^*$ is a vector space, we have by linearity that for linear functionals $L$ and $M$ and field elements $a,b\in \mathbb{C}$, 

$$ \langle aL+bM \mid p(x) \rangle = a\langle L \mid p(x) \rangle + b\langle M \mid p(x) \rangle $$

It is important then to note that since linear functionals are uniquely determined by the action on a basis, we know that $L$ is uniquely determined by the sequence of constants $ \langle L \mid x^n \rangle $.

The formal power series $f$ defined above defines a linear functional on $P$ if we define the following;

\begin{equation} \langle f(t) \mid x^n \rangle = a_n \end{equation}

for all nonnegative integers.  Thus, the formal power series $t^k$ gives

$$\langle t^j \mid x^n \rangle=n!\delta_{n,j}$$

where $\delta_{n,j}$ is the Kronecker delta.  Something to take note of then is that any linear functional $L\in P^*$ has the form of $f(t)$.  If then

\begin{equation}
f_L(t)=\sum_{j=0}^\infty {\langle L \mid x^j \rangle}\frac{t^j}{j!}
\end{equation}

we have that $f_L(t)=L$ as linear functionals.  Defining a map $L\rightarrow f_L(t)$, it can be shown this map is a vector space isomorphism and we can now think of linear functionals as formal power series.  

Let $$h(t)=f(t)+g(t)=\sum_{j=0}^\infty{a_j\frac{t^j}{j!}}+\sum_{j=0}^\infty{b_j\frac{t^j}{j!}}=\sum_{j=0}^\infty{(a_j+b_j)\frac{t^j}{j!}}$$  and $$ j(t)=f(t)g(t)=\left(\sum_{j=0}^\infty{a_j\frac{t^j}{j!}}\right)\left(\sum_{j=0}^\infty{b_j\frac{t^j}{j!}}\right)= \sum_{j=0}^\infty\left[\sum_{i=0}^j\binom{j}{i}a_ib_{j-i}\right]\frac{t^j}{j!}$$

Then

\begin{equation} \langle h(t) \mid x^n \rangle = a_n+b_n \end{equation}

and

\begin{equation} \langle j(t) \mid x^n \rangle = \sum_{i=0}^j\binom{j}{i}a_ib_{j-i} \end{equation}

Noticing then the relationship between the formal power series have with the linear functionals, we can show then that 

\begin{equation}
\langle f+g \mid x^n \rangle = \langle f \mid x^n \rangle + \langle g \mid x^n \rangle
\end{equation}

\begin{equation}
\langle fg \mid x^n \rangle = \sum_{k=0}^n\binom{n}{k}\langle f \mid x^k \rangle \langle g \mid x^{n-k} \rangle
\end{equation}

and it is these operations that allow us to extend our vector space idea and can now label $\mathcal{F}$ as an algebra structure.  In fact, this structure is known as the \it{umbral algebra}.

\begin{ex}
$f(t)=e^{yt}$

$$\langle e^{yt}\mid x^n \rangle =\left\langle \sum_{j=0}^\infty \frac{(yt)^j}{j!} \middle| x^n\right\rangle=\left\langle \sum_{j=0}^\infty y^j\frac{t^j}{j!} \middle| x^n\right\rangle=y^n$$

and

$$\langle e^{yt} \mid p(x) \rangle = \left\langle e^{yt} \middle| \sum_{k=0}^nc_kx^k \right\rangle=\sum_{k=0}^n{c_k}\langle  e^{yt} \mid x^k \rangle=\sum_{k=0}^n{c_k}y^k=p(y)$$

\end{ex}

\begin{ex}
$g(t)=f'(t)$

$$\langle g(t) \mid x^n \rangle =\langle f'(t) \mid x^n \rangle =\left\langle \frac{d}{dx}\sum_{j=0}^\infty a_j\frac{t^j}{j!} \middle| x^n\right\rangle=\left\langle \sum_{j=0}^\infty a_{j+1}\frac{t^j}{j!} \middle| x^n\right\rangle=a_{n+1}$$
\end{ex}

\begin{prop}
$$\langle f^{(k)}(x) \mid x^n \rangle=a_{n+k}$$
\end{prop}

\begin{ex}
$f(t)=\frac{e^x-1}{x}$

Note that

$$\frac{e^x-1}{x}=\frac{1}{x}\sum_{j=1}^\infty\frac{x^j}{j!}=\sum_{j=1}^\infty\frac{x^{j-1}}{j!}=\sum_{j=0}^\infty\frac{x^j}{(j+1)!}=\sum_{j=0}^\infty{\frac{1}{(j+1)}}\frac{x^j}{j!}$$

Therefore, 

$$\left\langle \frac{e^x-1}{x} \middle| x^n \right\rangle = \frac{1}{n+1}$$
\end{ex}

\begin{ex}
$f(t)=\frac{e^x-1-x}{x^2}$

Note that

$$\frac{e^x-1-x}{x^2}=\frac{1}{x^2}\sum_{j=2}^\infty\frac{x^j}{j!}=\sum_{j=2}^\infty\frac{x^{j-2}}{j!}=\sum_{j=0}^\infty\frac{x^j}{(j+2)!}=\sum_{j=0}^\infty{\frac{1}{(j+2)(j+1)}}\frac{x^j}{j!}$$

Therefore,

$$\left\langle \frac{e^x-1-x}{x^2} \middle| x^n \right\rangle = \frac{1}{(n+2)(n+1)}$$
\end{ex}

\begin{prop}
It makes sense then that if $T_n(x)$ is the Taylor polynomial

$$T_n(x)=\sum_{j=0}^n\frac{x^j}{j!}$$ 

then

$$\left\langle \frac{e^x-T_{k-1}(x)}{x^k} \middle| x^n \right\rangle = \frac{1}{(n+k)_k}$$

where $(n+k)_k=(n+k)(n+k-1)...(n+2)(n+1)$
\end{prop}

\begin{ex}
Replacing $x^n$ with an arbitrary polynomials $p(x)=c_0+c_1x+...+c_nx^n$

\begin{eqnarray*}
\left\langle \frac{e^x-1}{x} \middle|   p(x) \right\rangle &=& >\left\langle
\frac{e^x-1}{x} \middle| c_0+c_1x+...+c_nx^n \right\rangle \\ >&=&c_0\left\langle
\frac{e^x-1}{x} \middle| 1 \right\rangle+c_1\left\langle
\frac{e^x-1}{x} \middle| x \right\rangle+...+c_n\left\langle
\frac{e^x-1}{x} \middle| x^n \right\rangle \\ &=&\frac{c_0}{1}+\frac{c_1}{2}+...+\frac{c_n}{n+1} \\ &=&\int_0^1[c_0+c_1x+...+c_nx^n]dx \\ &=&\int_0^1p(x)dx
\end{eqnarray*}
\end{ex}

\begin{ex}

\begin{eqnarray*}
\left\langle \frac{e^x-1-x}{x^2} \middle|   p(x) \right\rangle &=& 
\left\langle
\frac{e^x-1-x}{x^2} \middle| c_0+c_1x+...+c_nx^n \right\rangle \\ 
&=&c_0\left\langle
\frac{e^x-1-x}{x^2} \middle| 1 \right\rangle+c_1\left\langle
\frac{e^x-1-x}{x^2} \middle| x \right\rangle+...+c_n\left\langle
\frac{e^x-1-x}{x^2} \middle| x^n \right\rangle \\ &=&\frac{c_0}{1\cdot  2}
+\frac{c_1}{2\cdot 3}+...+\frac{c_n}{(n+1)(n+2)} \\ >&=&\int_0^1\left[\int_0^1(c_0+c_1y+...+c_ny^n)dy\right]dx \\ &=&\int_0^1\int_0^1p(y)dydx
\end{eqnarray*}
\end{ex}


\begin{prop}
$$\left\langle \frac{e^x-T_{k-1}(x)}{x^k} \middle|   p(x) \right\rangle =\underbrace{\int_0^1 \int_0^1 \int_0^1}_{k\text{ times}}p(x_1)dx_1dx_2...dx$$
\end{prop}

\subsection{Preliminaries - Formal Power Series as Linear Operators}

Let 

\begin{equation} t^kx^n=(n)_kx^{n-k}
\end{equation}

It is clear that $t^k$ then acts as the $k$-th derivative on the monomial $x^n$.  Now if we consider a formal power series acting on $x^n$, we see that


\end{document}

编辑:我知道这可能会被人反对,但我还是把整个代码贴出来了。我对 TeX 还比较陌生,而且我自学的,从未正式教过,所以我很难根据我看到的回复找到问题所在。如果我这样做违反了任何规则,我很抱歉。

相关内容